2015
DOI: 10.1096/fj.14-269860
|View full text |Cite
|
Sign up to set email alerts
|

Cm-p5: an antifungal hydrophilic peptide derived from the coastal mollusk Cenchritis muricatus (Gastropoda: Littorinidae)

Abstract: Antimicrobial peptides form part of the first line of defense against pathogens for many organisms. Current treatments for fungal infections are limited by drug toxicity and pathogen resistance. Cm-p5 (SRSE-LIVHQRLF), a peptide derived from the marine mollusk Cenchritis muricatus peptide Cm-p1, has a significantly increased fungistatic activity against pathogenic Candida albicans (minimal inhibitory concentration, 10 mg/ml; EC 50 , 1.146 mg/ml) while exhibiting low toxic effects against a cultured mammalian ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 65 publications
(69 reference statements)
2
47
0
Order By: Relevance
“…18 Here, we present the intrinsic antifungal activity of the citric acid-coated MnFe 2 O 4 -NPs and the improvement of their antifungal activity when these nanoparticles were conjugated with a 12 aa peptide named Cm-p5. 19 This peptide is derived from Cm-p1, which is an MS-MS sequence found in a tryptic chromatographic fraction from the whole animal extract (Cenchritis muricatus [Gastropoda: Littorinidae], Linnaeus, 1758), which was positive for antimicrobial activity. We previously demonstrated that such sequence belongs to the original invertebrate, but we do not know if the corresponding peptide naturally acts as an AMP or if it is part of a major protein potentially undergoing cleavage by induction or not.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Here, we present the intrinsic antifungal activity of the citric acid-coated MnFe 2 O 4 -NPs and the improvement of their antifungal activity when these nanoparticles were conjugated with a 12 aa peptide named Cm-p5. 19 This peptide is derived from Cm-p1, which is an MS-MS sequence found in a tryptic chromatographic fraction from the whole animal extract (Cenchritis muricatus [Gastropoda: Littorinidae], Linnaeus, 1758), which was positive for antimicrobial activity. We previously demonstrated that such sequence belongs to the original invertebrate, but we do not know if the corresponding peptide naturally acts as an AMP or if it is part of a major protein potentially undergoing cleavage by induction or not.…”
mentioning
confidence: 99%
“…59 In this sense, Cm-p5 is not an amphipathic peptide, and its antifungal activity does not depend on its amino-terminal group. 19 Also, the mechanism of action of this peptide is related to interactions with the fungal cell surface; therefore, it is possible to have a synergistic antifungal action in the conjugate between the peptide and MNPs. In the same way, the immobilization of the AMP nisin to multiwalled carbon nanotubes improved the antibacterial and antibiofilm properties of noncoated carbon nanotubes.…”
mentioning
confidence: 99%
“…The secondary structure of AI-hemocidin 2 was investigated in different environments, including 10 mM PBS solution and 50% trifluoroethanol solution by circular dichroism (CD) spectroscopy [ 43 ]. As illustrated in Figure 4 A, peptides displayed random coil conformations in PBS.…”
Section: Resultsmentioning
confidence: 99%
“…The secondary structures of AI-hemocidin 2 in mimicking aqueous environment and mimicking the hydrophobic environment of the microbial membrane conditions were measured using a J-820 spectropolarimeter (Jasco, Tokyo, Japan) [ 43 ]. The spectra were recorded at a scanning speed of 10 nm/min at wavelengths range from 195 to 250 nm in 10 mM PBS and 50% TFE.…”
Section: Methodsmentioning
confidence: 99%
“…Another potent interesting antimicrobial peptide is Cm-p5, isolated from the mollusk Centrichis muricatus. Its prospection was performed after the tryptic fragmentation of a chromatographic fraction containing isolated peptides of C. muricatus analyzed by MS/MS, which generated a new candidate sequence (López-Abarrategui et al 2015). From bioinformatics analyzes, a series of variant peptides was theoretically proposed based on the sequence, and these were previously evaluated against C. albicans fungus.…”
Section: Promising Amps With Potential Therapeutic Properties Againstmentioning
confidence: 99%